(untitled) (PRÁXIS EM SAÚDE, 2025)
This work is a case study of one of the results of the master’s research "A Look at the Caregiver: The Emotional Experiences of Mothers of Children with ASD in Relation to the Diagnosis." The aim of this study is to demonstrate the importance of listening to mothers of children with ASD. The method used is qualitative and consists of a case study of one of the mothers interviewed for the research that gave rise to this summary. The results point to a scenario in which mothers of children with ASD experience loneliness, lack of support, and few opportunities to process the emotions arising from their child’s diagnostic process. For this reason, listening to these mothers proved to be an important resource in helping them face and experience the emotions related to the ASD diagnosis process.